2012
DOI: 10.1016/j.molcel.2012.08.026
|View full text |Cite
|
Sign up to set email alerts
|

The p23 Molecular Chaperone and GCN5 Acetylase Jointly Modulate Protein-DNA Dynamics and Open Chromatin Status

Abstract: SUMMARY Cellular processes function through multi-step pathways that are reliant on the controlled association and disassociation of sequential protein complexes. While dynamic action is critical to propagate and terminate work, the mechanisms used to disassemble biological structures are not fully understood. Here, we show that the p23 molecular chaperone initiates disassembly of protein-DNA complexes and that the GCN5 acetyltransferase prolongs the dissociated state through lysine acetylation. By modulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 48 publications
2
36
0
Order By: Relevance
“…Besides phosphorylation, HSF1 is acetylated, sumoylated, and ubiquitinated [11]. While the significances of these modifications are not completely understood, lysine acetylation within the DNA binding domain can inhibit DNA interactions whereas acetylation of the central regulatory domain deters degradation of HSF1 [12], [13], and [14]. Hence, modification of select HSF1 lysines is a potent means to control the HSR and support cell vitality.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides phosphorylation, HSF1 is acetylated, sumoylated, and ubiquitinated [11]. While the significances of these modifications are not completely understood, lysine acetylation within the DNA binding domain can inhibit DNA interactions whereas acetylation of the central regulatory domain deters degradation of HSF1 [12], [13], and [14]. Hence, modification of select HSF1 lysines is a potent means to control the HSR and support cell vitality.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that the GCN5 acetyltransferase selectively targets HSF1 lysine 80 (K80), which stabilizes HSF1 to DNA, whereas K80 is one of many residues modified by the P300 acetyltransferase [13] and [14]. In either case, acetylation of K80 impedes HSF1 DNA binding activity and limits the HSR.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two SIRT1 regulatory factors, AROS and DBC1, also affect HSF1 acetylation status and activation, broadening the acetylation regulatory network (Raynes et al 2013). Brian Freeman (University of Illinois, Urbana-Champaign, USA) presented both sides of the coin, documenting roles for both deacetylation and histone (more appropriately termed lysine) acetyltransferases (HATs/KATs) (Zelin et al 2012). In vitro acetylation was shown to block DNA binding by HSF1, and overexpression of the KAT GCN5 reduced hsp70 expression in human cells, consistent with prior data.…”
Section: New Insights Into Hsf Regulationmentioning
confidence: 99%